COTTON PRODUCTION IN INDIA: AN ECONOMIC ANALYSIS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2016)
Cotton is one of the most important and ancient crop of the world. It plays a very signification role in the economic,political and social affairs of the world. In India, cotton is cultivated as an important cash crop and used as fabric since time immemorial. Ancient texts of India like Rig Veda, Dharmashastra etc. mention the use of cotton. There are evidences to indicate that India had been the centre of important textile industry as early as 1500 BC. At present, Indian textile industry with more than 1062 textile mills constitutes one of the largest contributor to the economy in terms of annual output and labour employed, both direct and indirect. A poverty line is the income required for a minimum consumption level of food,clothing, shelter, transport, health care, and other necessary items. In 1979, the Task Force on Projections of Minimum Needs and Effective Consumption Demand defined the poverty line as the per capita consumption expenditure level at which the average daily calorie requirement were met on the basis of the all-India consumption basket using 1973–1974 data from the National Sample Survey (NSS) 28th round. The task forceused the age/sex/activity-specific calorie allowances recommended by the Nutrition Expert Group to estimate the average dailyper capita requirement for rural and urban areas (2,400 kilocalories in rural areas and 2,100 kilocalories in urban areas), usingtheir respective population structures as projected for 1982–1983. Thus, to the extent the data permitted, the age, sex, andoccupational differentials in the population’s daily calorie requirement were captured in the average norms.